Deciphering the Anti-Aflatoxinogenic Properties of Eugenol Using a Large-Scale q-PCR Approach - Caceres, Isaura; El Khoury, Rhoda; Medina, Angel; Lippi, Yannick; Naylies, Claire; Atoui, Ali; El Khoury, André; Oswald, Isabelle P.; Bailly, Jean-Denis; Olivier Puel (MDPI, 2016)
Produced by several species of Aspergillus, Aflatoxin B1 (AFB1) is a carcinogenic mycotoxin contaminating many crops worldwide. The utilization of fungicides is currently one of the most common methods; nevertheless, their use is not environmentally or economically sound. Thus, the use of natural compounds able to block aflatoxinogenesis could represent an alternative strategy to limit food and feed contamination. For instance, eugenol, a 4-allyl-2-methoxyphenol present in many essential oils, has been identified as an anti-aflatoxin molecule. However, its precise mechanism of action has yet to be clarified. The production of AFB1 is associated with the expression of a 70 kB cluster, and not less than 21 enzymatic reactions are necessary for its production. Based on former empirical data, a molecular tool composed of 60 genes targeting 27 genes of aflatoxin B1 cluster and 33 genes encoding the main regulatory factors potentially involved in its production, was developed. We showed that AFB1 inhibition in Aspergillus flavus following eugenol addition at 0.5 mM in a Malt Extract Agar (MEA) medium resulted in a complete inhibition of the expression of all but one gene of the AFB1 biosynthesis cluster. This transcriptomic effect followed a down-regulation of the complex composed by the two internal regulatory factors, AflR and AflS. This phenomenon was also influenced by an over-expression of veA and mtfA, two genes that are directly linked to AFB1 cluster regulation.
Keywords: Aflatoxin B; Aspergillus flavus; aflatoxinogenesis; molecular tool; gene regulation; eugenol